Polyvictimization and Depressive Symptomatology in Adolescents: Evaluation of the Role of School Social Climate. Issue 3 (27th May 2022) - Morlat, Pantxika; Lei, Chi Weng; Tse, Sing Ying; Guerra, Cristóbal
Abstract: The purpose of the current study is to examine the relationship between polyvictimization, school social climate, and depression in adolescents. Authors also looked at whether school social climate acts as a moderator of the interaction between polyvictimization and depressive symptoms. Furthermore, to have a deeper analysis, they included—as control variables—factors that have been shown in previous research to have an impact on depression, including age, gender discrimination, family support, and mood control. In total, 411 Chilean adolescents participated in the study from public (72.2 percent), semiprivate (17.4 percent), and private schools (10.4 percent). Four paper-based instruments were used to measure school social climate, depression, family support, and polyvictimization, and additional information was solicited with a sociodemographic data questionnaire. Regression analysis showed that both polyvictimization (β = .10, p = .03) and school social climate (β = –.10, p = .03) were predictors of depressive symptomatology. However, the interaction between polyvictimization and school social climate was not significant (β = .07, p = .73).